2013
DOI: 10.4253/wjge.v5.i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Repeat colonoscopy’s value in gastrointestinal bleeding

Abstract: There is clinical value of repeating a colonoscopy for recurrent lower gastrointestinal bleeding, especially within the first year after the index procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The intestinal mucosal examination coverage ratio can reach more than 86% when DAE is performed via both the oral and anal route. The diagnosis rate for OGIB patients with overt bleeding has been reported to range within 41-73% [8,9]. In the present study, it was found that the overt bleeding group had a diagnosis rate of 73.7%.…”
Section: Gastroenterology Research and Practicesupporting
confidence: 50%
See 1 more Smart Citation
“…The intestinal mucosal examination coverage ratio can reach more than 86% when DAE is performed via both the oral and anal route. The diagnosis rate for OGIB patients with overt bleeding has been reported to range within 41-73% [8,9]. In the present study, it was found that the overt bleeding group had a diagnosis rate of 73.7%.…”
Section: Gastroenterology Research and Practicesupporting
confidence: 50%
“…VCE is safe, efficient, and noninvasive but presents with difficulties in localizing the lesion site and in the inability to perform biopsy and treat the lesion on site. DAE has the advantages of performing biopsies, repeated observation, polypectomy, drug injection, and other surgical operations [6][7][8][9]. DAE encompasses double-balloon enteroscopy (DBE) and singleballoon enteroscopy (SBE), which was developed based on DBE.…”
Section: Introductionmentioning
confidence: 99%